Peroneal Tendon Tears: We Should Consider Looking at the Muscle Instead. Issue 22 (15th November 2018) - Res, Lodewijk C. S.; Dixon, Tonya; Lubberts, Bart; Vicentini, Joao R. T.; van Dijk, Pim A.; Hosseini, Ali; Guss, Daniel; DiGiovanni, Christopher W.
Abstract : Introduction: The purpose of this study was to determine whether tears of the peroneus brevis (PB) tendon correlate with increased fatty infiltration of the PB muscle on MRI compared with musculature without clinical evidence of peroneal pathology. Methods: Ankle MRI scans of patients with PB tendon tearing (tear group) were compared with those of patients without clinical evidence of peroneal pathology (control group). Two reviewers graded the PB muscle belly according to the Goutallier classification. Results: Thirty patients were included in each group. The mean Goutallier scores for the tear and control groups were 0.52 (±0.72) and 0.05 (±0.15), respectively ( P = 0.0019). The level of interobserver agreement between reviewers was moderate (intraclass correlation coefficient = 0.75; 95% confidence interval, 0.57 to 0.85). Discussion: Patients with PB tendon tear demonstrate markedly higher grades of fatty degeneration compared with patients without peroneal pathology. The Goutallier classification may become a valuable instrument for assessing the severity of a PB tear. Level of Evidence: Level III—diagnostic study